Feasibility study and simulation of a 4 MW solar power plant design using PVSyst in Oefafi Village, Kupang, Indonesia - Pranata, Nicholas; Saputri, Fahmy Rinanda; Akbar, Agie Malki (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
Indonesia has a vast amount of potential for renewable energy, with many places still experiencing inaccessibility and inadequacy to electricity. One of the places, Kupang in East Nusa Tenggara, suffers a deficit of 4 MW at night along with a blackout despite the implementation of the Oelpuah Solar Power Plant that can produce 5 MW. Thus, this study presents a feasibility study and simulation of additional solar power plant implementation using PVSyst based on geospatial analysis by ArcGIS to point down the desired location, namely Oefafi. The results produce 7,212,139 kWh/year (almost 20 MWh/day using 6,552 modules of Jinkosolar 610 Wp JKM-610N-78HL4- BDV, 274 units of Growatt 12KTL3-X inverters, and 2000 BYD B-Box PRO 2.5 1,024 V 5,200 Ah battery. The losses of the systems mostly come from temperature loss in PV. The total installation cost is 51 billion IDR with a payback period of 8.3 years, NPV of 6.6 billion IDR, and IRR of 10.62% for an electricity tariff of 1,000 IDR/kWh. The amount of greenhouses saved accounts for 134,110.3 tCO2. This will help in filling the 4MW deficit while also potentially providing to other unsupplied regions. Future research may use other software for comparison and give better explanations.